An Overview on ELT Scenario in Surkhet - Sharma, Dhirendra Prasad (Journal of NELTA Surkhet, 2015)
The main purpose of this article is to analyze the ELT scenario of community based schools in Surkhet district. This paper, presents an introduction of ELT curriculum of English in school level, current status of ELT achievement in Surkhet district, issues, challenges and problems overwhelmed around ELT in community-based schools, strategies to enhance the competence and performance of teachers towards ELT for pedagogical recommendation and implication. From the close observation of some schools and teachers’ class and official data related to ELT achievement, this article suggests that creating happy and child friendly environment towards learning second language, demand based trainings, use of relevant teaching aids in language classroom, effective continuous assessment system, monitoring, and awareness of the stakeholders towards English language teaching contribute a lot for making effective English classes in the context of Surkhet district. Journal of NELTA Surkhet Vol.4 2014: 41-47